KEBENARAN ILMIAH DAN KECERDASAN BUATAN: REFLEKSI FILSAFAT ILMU DALAM ERA DIGITAL - Muhammad Fachri Hafizh Saleh (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2025)
The development of Artificial Intelligence (AI) has led to an epistemological shift in how humans understand and produce knowledge. This article aims to re-examine the concept of scientific truth within the framework of the philosophy of science in the digital era, emphasizing the relationship between humans, machines, and truth. Using a qualitative-descriptive approach through literature studies from Western and Islamic philosophies—including the thoughts of Karl Popper, Thomas Kuhn, and Al-Ghazali—the study finds that AI challenges human epistemic boundaries by introducing a form of “algorithmic truth” that is predictive yet not always empirical. From an axiological standpoint, AI must be directed toward human welfare through ethical and moral values. The study concludes that integrating scientific truth with ethical values is essential to address the epistemological challenges of the digital age.